1993
DOI: 10.1086/648220
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Erosion Thresholds, Channel Networks, and Landscape Morphology Using a Digital Terrain Model

Abstract: To investigate the linkage between erosion process and channel network extent, we develop two simple erosion threshold theories driven by a steady state runoff model that are used in the digital terrain model TOPOG to predict the pattern of channelization. TOPOG divides the land surface into elements defined by topographic contours and flow lines, which can be classified as divergent, convergent and planar elements. The calibration parameter for the runott model is determined using empirical evidence that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
222
0
11

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(240 citation statements)
references
References 15 publications
6
222
0
11
Order By: Relevance
“…The specific catchment area contributing to flow at any particular location is useful for determining relative saturation and generation of runoff from saturation excess in models such as TOPMODEL [Beven and Kirkby, 1979;Beven et al, 1984;Wood et al, 1990]. Specific catchment area together with other topographic parameters has also been used in the analysis of processes such as erosion and landslides [Dietrich et al, 1992[Dietrich et al, , 1993Wu, 1993 The earliest and simplest method for specifying flow directions is to assign flow from each pixel to one of its eight neighbors, either adjacent or diagonal, in the direction with steepest downward slope. This method, designated D8 (eight flow directions), was introduced by O'Catlaghan and Mark [1984] and has been widely used [Marks et Dispersion is inherent in any method (including the one I describe below) that assigns flow from one pixel to more than one downslope neighbor and manifests itself in terms of spreading of flow from a single pixel.…”
Section: Introductionmentioning
confidence: 99%
“…The specific catchment area contributing to flow at any particular location is useful for determining relative saturation and generation of runoff from saturation excess in models such as TOPMODEL [Beven and Kirkby, 1979;Beven et al, 1984;Wood et al, 1990]. Specific catchment area together with other topographic parameters has also been used in the analysis of processes such as erosion and landslides [Dietrich et al, 1992[Dietrich et al, , 1993Wu, 1993 The earliest and simplest method for specifying flow directions is to assign flow from each pixel to one of its eight neighbors, either adjacent or diagonal, in the direction with steepest downward slope. This method, designated D8 (eight flow directions), was introduced by O'Catlaghan and Mark [1984] and has been widely used [Marks et Dispersion is inherent in any method (including the one I describe below) that assigns flow from one pixel to more than one downslope neighbor and manifests itself in terms of spreading of flow from a single pixel.…”
Section: Introductionmentioning
confidence: 99%
“…These studies underlined the difficulties encountered when linking local responses (sub-basins or hillslopes) to this global behaviour, and this aim has been one of the main issues for geomorphologists since the 1970s (Veltri et al 1996;Rodriguez-Iturbe and Rinaldo 1997;Schmitz and Cullmann 2008). A few studies have successfully shown that the network organization plays a key role on hydrological functionality (Dietrich et al 1993;Vogt et al 2003). The CA RUICELL partially overcomes such difficulties and also implicitly captures the channel network structure and its influence on flood through scales.…”
Section: Methodsmentioning
confidence: 99%
“…teria (e.g., Montgomery and Dietrich, 1992;Dietrich et al, 1993) based on flow accumulation and surface slope, plan (contour) curvature, and flow length over which these criteria are met (Miller et al, 2002(Miller et al, , 2015.…”
Section: Dem and Stream Networkmentioning
confidence: 99%